Experimental investigation into vibration control of stern structure excited by propeller forces - Shengpeng JIANG (Zhongguo Jianchuan Yanjiu, 2021)
ObjectivesTo reduce the vibration of stern structure excited by lateral propeller forces, the application of vibration isolation, vibration blocking masses and damping coating is carried out.MethodsFirst, the vibration transmission characteristics of the shaft-stern coupled system are obtained through vibration testing, then the lateral excitation mainly transmits to the stern structure through the rear stern bearing is suppressed using three control methods based on the test results. Finally the validity of the respective proposed methods is verified. ResultsThe test results show that vibration isolation has limited effectiveness in reducing vibration in the low to medium frequency range due to the limited range of stiffness variation; vibration blocking masses are more effective in isolating vibration transmission to the stern structure; and damping coating has significant effect on the attenuation of vibration in the high frequency range. The acceleration level of the stern structure is reduced by at least 6 dB under the comprehensive application of the three control methods.ConclusionsThe results obtained in this study have reference value for the vibration control of the stern structures excited by propeller forces.